THE ROLE OF THE NURSE IN THE PREVENTION OF METABOLIC SYNDROME (World Science, 2020)
The article reveals the relevance and essence of the metabolic syndrome problem. According to studies, in developed countries 15-25% of people aged 40-70 years have symptoms of metabolic syndrome. The role of a nurse in the effective prevention and treatment of metabolic syndrome is presented. An improvement in the well-being and quality of life of patients with metabolic syndrome after correction of the patient's lifestyle was noted.